7(3x-10)=3(7x-5)

Simple and best practice solution for 7(3x-10)=3(7x-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(3x-10)=3(7x-5) equation:


Simplifying
7(3x + -10) = 3(7x + -5)

Reorder the terms:
7(-10 + 3x) = 3(7x + -5)
(-10 * 7 + 3x * 7) = 3(7x + -5)
(-70 + 21x) = 3(7x + -5)

Reorder the terms:
-70 + 21x = 3(-5 + 7x)
-70 + 21x = (-5 * 3 + 7x * 3)
-70 + 21x = (-15 + 21x)

Add '-21x' to each side of the equation.
-70 + 21x + -21x = -15 + 21x + -21x

Combine like terms: 21x + -21x = 0
-70 + 0 = -15 + 21x + -21x
-70 = -15 + 21x + -21x

Combine like terms: 21x + -21x = 0
-70 = -15 + 0
-70 = -15

Solving
-70 = -15

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 0.6x+22=28 | | 5.4X+.4=3.4 | | 7x+3-(2x-1)= | | 14y-8-10y=0 | | (Y-2)+y=18 | | .6k-.1k=.5k-1 | | x^5-3x^4+4x^3-8x^2+16=0 | | ln(6x-6)=13 | | 4-(x+9)=-x-4-5 | | -4s=-34 | | n-5*2=5 | | 8y^2+36y-72=0 | | 6-(-8)=0 | | 11m+3=8m-18 | | 575=35x-75y | | 2(b-5)=5(b+5)-17 | | 2(y+3)=2y-6(y+5) | | m^2+3=0 | | 5m-3=2(m+3) | | x^2+72=17x | | 35x+50y= | | 162+16m=354 | | 15x^2-10x+15=0 | | 15x^2-10x+15=0 | | 14-7t-16=8t+25-6t | | 4m^2+9=0 | | 4(1h+2)=3(h-2) | | 6x+3-2x=2x+7 | | -12m-3=-12 | | -70-3x+x^2=0 | | 5y+40=-2y-9 | | -0.5m=-9 |

Equations solver categories